Relationship between Agriculture Growth and the Unemployment Rate in Iraq (1991–2022) - Abdallah Sharif, Nabard; Ali Mohammed, Burhan; Nwri Rostam, Biaban (Journal of Economics and Administrative Sciences, 2024)
Purpose: The objective of this study is to analyze the relationship betweenagriculture development and unemployment rate for the period of 1991-2-2022 in Iraq.Theoretical framework: In the context of agricultural employment, agriculture is recognised as a crucial component of economic advancement and emphasises the significance of efficiently utilising all available resources, including human resources (Alsudani & Al-Hiyali, 2021). Moreover, the growth of agricultural and the unemployment rate have been used as two indicators to evaluate the significance of the agriculture sector(Jongerden et al., 2019).Design/methodology/approach: In order to examine whether there exists a real correlation between unemployment rate and agriculture growth in Iraq, we utilize yearly secondary data and apply extensive methodology that includes unit root tests, correlation analysis, co-integration tests, and the autoregressive distributed lag (ARDL) approach.Findings: the results of emperical examinations highlight a negative relationship between agricultural growth and the unemployment rate; that is, as agriculture growth increases, so does the unemployment rate decrease.Research, Practical & Social implications: The findings can provide insights for well-informed policy decisions and strategies to promote sustainable growth and employment generation in Iraq. In addition, for future research we suggest to include more macroeconomic variables in oreder to have intensive understanding real impacts of agriculture sector on economic growth and laboure force of countries.Originality/value: The results document that the connection between both agriculture development and unemployment rate is not positive, it means that unemployment rate will decrease if growth in agriculture increase.